2019
DOI: 10.12659/msm.919307
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Status in Pregnant Women in Southern China and Risk of Preterm Birth: A Large-Scale Retrospective Cohort Study

Abstract: Departmental sources Background: The influence of maternal vitamin D on pregnancy outcomes, including preterm birth (PTB), is unclear due to different experimental designs and study populations (patient race and sample size) of previous studies. We aimed to investigate the relationship between 25-hydroxyvitamin D (25[OH] D) levels and PTB among pregnant women in southern China. Material/Methods: A total of 11 641 pregnant women were retrospectively enrolled between January 2016 and April 2019. Vitamin D concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 23 publications
1
12
0
Order By: Relevance
“…8 Consistently, our previous studies also have shown that in Guangzhou, a city in southern China with a subtropical climate and sufficient sunlight exposure, children and pregnant women tend to have vitamin D deficiency or insufficiency. 9,10 Pandemic-related confinement reduces the amount of time spent outdoors, particularly among children. It is likely that 25(OH)D levels in children were lower during the period of confinement than otherwise.…”
Section: Introductionmentioning
confidence: 99%
“…8 Consistently, our previous studies also have shown that in Guangzhou, a city in southern China with a subtropical climate and sufficient sunlight exposure, children and pregnant women tend to have vitamin D deficiency or insufficiency. 9,10 Pandemic-related confinement reduces the amount of time spent outdoors, particularly among children. It is likely that 25(OH)D levels in children were lower during the period of confinement than otherwise.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, a cohort study based on a prospective community research did not find any evidence showing that vitamin D status during early pregnancy was associated with pregnancy-related hypertension in women who did not have children [18]. In one of our previous studies, prenatal vitamin D levels did not have any effect on the birth weight of premature infants [19].…”
Section: Discussionmentioning
confidence: 66%
“…One year later (2017), Zhou [25] et al, in their meta-analysis which included 24 articles (18 were observational studies and six were randomized clinical trials), concluded that maternal 25-OHD deficiency was associated with an increased risk of PB (OR = 1.25). On the other hand, several previous studies did not identify an association between low serum 25(OH)D concentrations/vitamin D deficiency and the risk of PB [18][19][20][21]. Recently, Lian et al, in their meta-analysis which included 24 studies, concluded that vitamin D deficiency in early and late pregnancy was not associated with increased risk of PB; however, they reported that vitamin D deficiency in the second trimester of pregnancy was associated with increased risk of PB [17].…”
Section: Discussionmentioning
confidence: 84%
“…Previous reports have shown that several maternal and perinatal adverse effects such as gestational diabetes, preeclampsia, PB and small for gestation age and intrauterine growth restriction are associated with low vitamin D levels in pregnancy [10,11]. Previous studies on the associations between vitamin D and Nutrients 2022, 14, 891 2 of 8 PB showed inconclusive results-while some of the studies showed that serum vitamin D levels are lower in women with PB and reported that vitamin D deficiency is associated with an increased risk of PB [10][11][12][13][14][15][16], other studies did not identify an association between low serum 25(OH)D concentrations/vitamin D deficiency and the risk of PB [17][18][19][20][21]. Moreover, most of these studies were conducted in countries outside Africa, with few published data on the association between serum 25(OH)D concentrations/vitamin D deficiency and the risk of PB in Africa [13,14].…”
Section: Introductionmentioning
confidence: 99%